Extent of Teachers' Knowledge of Required Skills in Distance Education in Jordan during the Coronavirus Pandemic - Suhair Mohammad Abdallah Alkhwaja; Wael Issa Saleh Seitan (Deanship of Scientific Research (DSR), the University of Jordan, 2022)
Objectives: The study aims to reveal the degree of teachers' knowledge of the skills required in distance education in Jordan during the Coronavirus pandemic, and whether it varies due to gender or stage. The study was applied in the second semester of the 2020 scholastic year. Methods: To achieve the results, a descriptive approach was implemented. The main study tool was a questionnaire that was designed after reviewing the educational literature and previous studies. It consisted of (17) paragraphs. The study population consisted of (4013) teachers from Kasbaet Amman, where the sample of the study members consisted of (300) teachers, who were chosen in a simple random method from the study population. Results: The results of the study indicate that the degree of teachers' knowledge of the required skills in distance education in Jordan during the Corona pandemic was moderate. The results also show that there are no statistically significant differences due to gender. There are statistically significant differences due to school stage in favor of kindergarten stage. Conclusions: In the light of the results of the study, the researchers recommend continuously training teachers on distance education skills and on how to design lessons according to models that adopt distance education. They also recommend reviewing curricula and developing them to suit the skills required for distance education, especially after the pandemic.